2022
DOI: 10.1177/21501319221111106
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection Treatment Outcomes in an At-Risk Underserved Population in Rhode Island

Abstract: Objectives: Within the United States (US), significant racial and ethnic disparities exist in the rates of latent TB infection (LTBI) and active TB disease. A disproportionate number of TB disease cases result from untreated LTBI among individuals born outside the US. This study evaluates LTBI treatment outcomes among an underserved, at-risk population in Rhode Island. Methods: A quantitative retrospective chart review of adult patients with a positive screening test assessed LTBI care cascade outcomes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…al. identified that the main gaps in the success of TPT were referral and initiation of treatment, 14 probably similar to the present study that shows only 10,8% of the estimated cases of TPT.…”
Section: Discussionsupporting
confidence: 91%
“…al. identified that the main gaps in the success of TPT were referral and initiation of treatment, 14 probably similar to the present study that shows only 10,8% of the estimated cases of TPT.…”
Section: Discussionsupporting
confidence: 91%